Synthesis, structure, and antimicrobial activity of aminated 5-chloro-6-nitrobenzofurazan with substituted anilines - I.V. Galkina; G.L. Takhautdinova; Kh.R. Khayarov; L.M. Yusupova; O.I Gnezdilov; A.V. Ilyasov; V.I. Galkin (Учёные записки Казанского университета: Серия Естественные науки)
A simple and efficient procedure for synthesis of nucleophilc aromatic substitution products in benzofurazan cycle on the basis of reactions of substituted anilines with 5-chloro-6-nitrobenzofurazan has been elaborated. The obtained products have a broad spectrum of antibacterial and antimycotic activity. The structure of compounds has been confirmed by IR-, NMR-spectroscopy and also by single-crystal X-ray analysis. Thermal stability of the products has been studied by the combined method of thermogravimetry and differential scanning calorimetry (TG-DSC).